Uji Kinerja Turbin Angin Sumbu Horizontal Dengan Tipe Bilah Inverse Taper Dengan Jari-Jari 1,3m Pada Kecepatan Angin Di Pekanbaru - Sibuea, Edwin Reinaldy; Agustina, Dinni; Martin, Awaludin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
The increasing needs of electrical energy and the limited amount of fossil fuel that keep reducing give a huge effect to the enhancement of renewable wind energy to grows rapidly, one of it is wind turbine. The purpose of this research is to study the performance of horizontal axis wind turbine with inverse taper blade. The wind turbine is place on a building with ±15m. The output power is measured under loading condition with 4.37 kg load. Acquired data were wind velocity, air temperature, constant load, and the shaft rotation speed. The result of the power test is 0.49 watt under wind velocity of 2.92 m/s and Tip Speed Ratio (TSR) 0.056 Keyword: Wind turbine, wind speed, inverse taper, TSR